THU0591 Assessing the readability and patient comprehension of medicine information sheets provided to patients by australian rheumatologists. (15th June 2017) - Oliffe, M; Johnston, J; Freeman, D; Bagga, H; Wong, PK
Abstract : Background: Literacy is "the ability to read and use written information and to write appropriately in a range of contexts". 1 Low literacy is associated with poorer health outcomes, including increased mortality. 2 Those accessing the healthcare system require adequate literacy to understand written instructions regarding medication, appointments and medication doses. We have previously shown in >200 rural and urban Rheumatology patients that <15% of patients had low health literacy and <1/3 of patients incorrectly followed dosing instructions for common Rheumatology drugs. 3 Up to 24% of US Rheumatology patients had a reading level of ≤8th grade. 4 These findings are concerning, as Rheumatologists often use medications such as MTX or bDMARDS with severe side effects. Rheumatologists often provide written information regarding these medications to patients. Objectives: To assess i) the readability of Patient Medicine Information Sheets (PMIS) regarding medications provided to patients by Australian Rheumatologists, and ii) patient comprehension of these documents. Methods: Thirty-one English-language PMIS from the Australian Rheumatology Association (ARA) website were assessed for readability using Readability Studio TM (Oleander Software). This software uses the number of sentences, words, syllables and characters in a sample of writing to estimate the required grade level and reading age of the target population using several readability scales (eg Flesch scale, Gunning Fog and Simple Measure of Gobbledygook, or SMOG). To assess comprehension, a random sample of 100 patients from MNCAC was asked to read an ARA PMIS about one of the following medications: MTX, NSAIDS, Adalimumab, Abatacept or prednisone. He/she then answered five multiple choice questions about the content. A time limit of 15 minutes for reading the PMIS and answering the questions was allowed.Approval was obtained from the local HREC as a low/negligible risk project. Results are expressed as mean ± sem. Results: The mean Flesch scale value (range 0–100, 0=very confusing; 100=very easy) of the 31 PMIS assessed was 51.1±0.6 (fairly difficult). The mean FORCAST grade level and reader age was 11±0 and 16–17 years, respectively. The mean Gunning Fog grade level was 11.4±0.1 with a reader age of 16–17 years. The mean SMOG grade level was 11.8±0.1 with a mean reader age of 16–17 years. At time of writing, comprehension was assessed in 7 of the planned 100 patients. So far, the mean number of correct answers was 3.2±0.5 (max. score of 5). Conclusions: The ARA PMIS are suitable for readers who have completed a grade level ≥11 with a reading age ≥16 years. A low literacy population (< grade 8) will probably struggle to understand the content. These findings need to be extended to the PMIS used in other countries and has implications for the design of better patient information material. References: Australian Government, Department of Education Employment and Training. The Australian Language and Literacy Policy. Canberra 1991. Baker DW et al. Arch Intern Med 2007;167:1503–1509. Wong PK et al. Medicine (Baltimore) 2014 Nov;93(25):e129. Swearingen CJ et al. J Clin Rheumatol 2010;16:359–364. Disclosure of Interest: None declared